الكلوية عند الأطفال دراسة استقلابية, سريرية, تشريحية, ووراثية لعينة من المرضى في مشفى تشرين الجامعي - Laeka, Anan (Latakia University Journal -Medical Sciences Series, 2019)
الحصيات الكلوية عند الأطفال دراسة استقلابية, سريرية, تشريحية, ووراثية لعينة من المرضى في مشفى تشرين الجامعي Our study objective was to evaluate urinary metabolic abnormality, a structural renal abnormality and collection of demographic and clinical manifestations in 44 patients (infants and adolescents), the study was established in Tishreen University Hospital. The patients underwent metabolic assessment, including 24-hour urine analysis, urine analysis , and stones composition analysis. About 89,3 % of the patients (n = 28) had an underlying metabolic abnormality that included hypercalciuria . Calcium Oxalate was found in 58,3 % patients . structural anomalies of the kidney and urinary tract were found in 18 % of the patientsof which pylo-urethral duplication was the most frequent one. Positive family history seems to be very important ( 81,3%) isolated risk factor. Conclusion : the present study was important as it analyzed the characteristics of pediatric patients with nephrolithiasis in our region. الهدف : تهدف الدراسة إلى إجراء تقييم للاضطرابات الاستقلابية و التشريحية و جمع المعلومات السريرية والوراثية عند 44 طفلاً و يافعاً . أجريت الدراسة في مشفى تشرين الجامعي بين شهري شباط 2017 -2018 , و ذلك بإجراء الاستقصاءات المخبرية لعينة بول 24 ساعة ( كالسيوم , حمض البول , الأكزالات , و السيترات) مع فحص بول و راسب ، بالإضافة إلى إجراء تحليل كيميائي للحصيات الكلوية . أظهرت الدراسة أن حوالي 89,3 % من المرضى الذين أجريت لديهم دراسة استقلابية ( 28 مريضاً ) لديهم اضطراب استقلابي , و الأكثر حدوثا كان ارتفاع كلس البول (71%) و أكثر الحصيات حدوثاً كانت أكزالات الكالسيوم بنسبة ( 58,3% ) . وجدت التشوهات التشريحية عند (18 %) من المرضى الذين تم استقصاؤهم , و أكثر التشوهات حدوثا هو تضاعف الحالب و الحويضة . يبدو أن القصة العائلية الإيجابية تمثل عامل خطورة كبير الأهمية عند ( 81,3 % ) من المرضى. النتيجة : أظهرت هذه الدراسة الهامة الخصائص الأساسية لداء الحصيات الكلوية عند الأطفال في منطقتنا.